Possession and deployment of nuclear weapons in South Asia: an assessment of some risks - Rajaraman, R.; Mian, Zia; Ramana, M.V. (2002)
This paper examines some of operational requirements and the dangers that come with the possibility that in the foreseable future India and Pakistan may deploy their nuclear arsenals. The authors first describe the analytical basis for the inevitability of accidents in complex high-technology systems. Then they turn to potential failures of nuclear command and control and early warning systems as examples. They go on to discuss the possibility and consequences of accidental explosions involving nuclear weapons and their delivery systems. Finally some measures to reduce these risks are suggested.
Keywords: Nuclear weapons